Congenital Myasthenic Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A new syndrome associated with a deficiency of acetylcholine receptor (AChR) and a short open-time of the AChR channel in a 5 year-old girl with myasthenic symptoms since birth is reported from the Neuromuscular Research Laboratory, Mayo Clinic, Rochester, MN.